Variación morfológica de la lagartija partenogenética Aspidoscelis rodecki (Squamata: Teiidae): implicaciones evolutivas y de conservación - Sandra P Elizalde-Rocha; Fausto R Méndez-de la Cruz; J. Fernando Méndez-Sánchez; Gisela Granados-González; Oswaldo Hernández-Gallegos (Revista de Biología Tropical, 2008)
La divergencia post-formación se ha utilizado para el reconocimiento de nuevas especies partenogenéticas. Actualmente, la lagartija partenogenética Aspidoscelis rodecki McCoy y Maslin 1962 es reconocida como una sola especie, que se originó de un híbrido partenogenético. Estudios previos han encontrado divergencia genética, en coloración y en características de historia de vida entre una población continental (Puerto Juárez) y una insular (Isla Contoy) en Quintana Roo, México. Se llevó a cabo un análisis merístico para evaluar la divergencia entre ambas poblaciones de A. rodecki. Se utilizaron 38 individuos de Puerto Juárez y 23 individuos de Isla Contoy. Se usaron nueve características merísticas y se realizaron análisis univariados (t de Student) y multivariados (análisis de componentes principales y análisis de variación canónica). De acuerdo a ambos análisis, Puerto Juárez es merísticamente distinguible de Isla Contoy. Ambas poblaciones difieren en cinco características merísticas y presentaron un alto porcentaje de clasificación en el análisis de variación canónica: 97% para Puerto Juárez y 100% para Isla Contoy. Una pequeña muestra de Isla Mujeres y un solo individuo de Punta Sam (continente) pueden representar otros grupos morfológicos. Con base en los patrones de variación fenotípica, A. rodecki es considerada como una sola especie partenogenética variable y prioritaria para la conservación. Debido a que cada población contiene una porción única de la variación de A. rodecki, Puerto Juárez e Isla Contoy merecen un manejo separado y se sugiere que cada una constituya una "Unidad Evolutiva Significativa" (ESU). Morphologic variation of the parthenogenetic lizard Aspidoscelis rodecki (Squamata: Teiidae): evolutionary and conservation implications. Post-formational divergence has been used for the recognition of new parthenogenetic species. Currently, the parthenogenetic lizard Aspidoscelis rodecki McCoy and Maslin 1962 is recognized as a single taxon that was derived from a single, parthenogenetically capable, hybrid. This lizard had been derived via hybridization between individuals of two gonochoristic species, Aspidoscelis angusticeps Cope 1878 and Aspidoscelis deppii Wiegmann 1834. The distribution of A. rodecki includes Isla Contoy and Isla Mujeres and the adjacent mainland of Quintana Roo, México. Previous studies have found post-formational divergence in genetic, chromatic and life-history characteristics among a continental population (Puerto Juárez) and an insular population (Isla Contoy). A meristic analysis was carried out to evaluate the morphological divergence among both populations of A. rodecki. We used 38 individuals from Puerto Juárez and 23 individuals from Isla Contoy. Nine meristic characters with discrimination value among species of the genus Aspidoscelis were used in both univariate (t-Student) and multivariate analyses (principal components and canonical variate analysis). According to both analyses, Puerto Juárez is meristically distinguishable from Isla Contoy. Both populations differ in five meristic characters and were a high correct classification in the canonical variate analysis: 97% of Puerto Juárez and 100% of Isla Contoy. A small sample from Isla Mujeres and a single specimen from Punta Sam (mainland) may represent different morphological groups. Due to the patterns of phenotypic variation, A. rodecki is considered as a single variable parthenogenetic species with high priority to conservation. The populations of A. rodecki have been extremely affected by the tourism developers. If the habitat of the parthenogenetic lizard (beach grasses) is allowed to stay, the expansion by the developers will not affect the survivorship of these populations. Nevertheless, the first sign of development is the total destruction of natural grasses that occurs on the beach, leaving only sand. There is a last chance to save the parthenogenetic lizard A. rodecki, but any effort will be useless without the support from the environmental authority of Mexico and cooperation from the developers. We suggest that Puerto Juárez and Isla Contoy receive separate management because they have unique portions of phenotypic variation of A. rodecki. The two lizard populations can be considered separate "Evolutionary Significant Units" (ESU). Rev. Biol. Trop. 56 (4): 1871-1881. Epub 2008 December 12.